Learning Styles and Study Habits of New University Students at a Public University in Mexico. - Niño, Shamaly Alhelí; Viloria, Esperanza; Santillán, Victoria Elena; Castellanos, Juan Carlos (Advances in Social Sciences Research Journal, 2019)
The objective of this research is to identify the learning styles and study habits of new students of the Education, Psychology, Communication, Sociology, and History undergraduate programs of the School of Humanities at the Mexicali Campus of Universidad Autónoma de Baja California (UABC), in Mexico. The method is quantitative, with a sample of 650 students. The inventories used are the survey applied upon admission to the School of Humanities, and adaptations of the Learning Styles and Study Habits Inventories. The questionnaires were answered online by students who were already enrolled in the 2016-2017 school year. A socio-demographic profile of the students was established based on the results: 73 % of enrolled students are female, and only 27 % are male. The majority (70 %) live with their families (father, mother, siblings); 75 % of students do not work; 90 % said they were single and 10 % were married. The predominant learning styles out of the 13 dimensions are the factors associated with effort and frustration tolerance (.99), followed by a single and structured focus of attention (.98) and intrinsic motivation (.94). The primary study habits in the aspect of optimization are reading 32.8 % and motivation to study 28.7 %. Conclusion: Comprehensive profiles that consider the sociodemographic background, learning styles and study habits are essential when dealing with new students.